COVID-19 transmission in dental practice during the pandemic: A questionnaire-based survey in private dental clinics in Japan - Hironori Sakai; Eiji Kondo; Hirokazu Tanaka; Tetsu Shimane; Shinichi Yamada; Hiroshi Kurita (Elsevier, 2023)
Background/purpose: The global coronavirus disease 2019 (COVID-19) pandemic continues to cause a significant impact on patient care due to its considerable transmissibility, morbidity, and mortality. The aim of this study was to investigate whether dental procedures performed at private dental clinics were associated with the occurrence of COVID-19 clusters and measures taken to prevent nosocomial infection of COVID-19. Materials and methods: An online questionnaire-based survey on clinical activities, infection control measures, and confirmed or probable COVID-19 cases among patients and clinical staff during the pandemic (February 2020 to September 2021) was administered to dentists at private dental clinics in Nagano prefecture, Japan. Almost all dentists engaged in dental treatment were actively implementing standard precautions. Results: Twenty-seven dental clinics provided dental care to infected patients (nine confirmed and eighteen probable), but there was no transmission from patients to staff. Ten clinics had staff who were infected, but none exhibited disease transmission from staff to patients. Conclusion: The results of this survey suggest that COVID-19 clusters might not occur in dental settings where appropriate protective measures are implemented.